2016
DOI: 10.1371/journal.pone.0144393
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Correlates of Emotional and Action Appraisals During Visual Processing of Emotional Scenes Depending on Spatial Frequency: A Pilot Study

Abstract: Visual processing of emotional stimuli critically depends on the type of cognitive appraisal involved. The present fMRI pilot study aimed to investigate the cerebral correlates involved in the visual processing of emotional scenes in two tasks, one emotional, based on the appraisal of personal emotional experience, and the other motivational, based on the appraisal of the tendency to action. Given that the use of spatial frequency information is relatively flexible during the visual processing of emotional sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 114 publications
1
2
0
Order By: Relevance
“…First, numerous studies have previously shown that, although LSF information is preferentially used at short exposure duration to enable efficient and rapid scene categorization, it does not follow that it is always used first to support visual recognition. Indeed, and as suggested by our results, HSF can also be extracted very early in the visual processing timecourse, and their preferential use would be determined by the demands of the visual task (Campagne et al, 2016;Harel & Bentin, 2009;Morrison & Schyns, 2001;Oliva & Schyns, 1997;Ozgen et al, 2006;Rotshtein et al, 2010;Schyns, 1998;Schyns & Oliva, 1994. For example, in Schyns and Oliva (1994), the perception of hybrids at short exposure duration of 30 ms was dominated by the HSF scene in 28% of the trials.…”
Section: Spatial Frequency Semantic Interferencesupporting
confidence: 70%
See 1 more Smart Citation
“…First, numerous studies have previously shown that, although LSF information is preferentially used at short exposure duration to enable efficient and rapid scene categorization, it does not follow that it is always used first to support visual recognition. Indeed, and as suggested by our results, HSF can also be extracted very early in the visual processing timecourse, and their preferential use would be determined by the demands of the visual task (Campagne et al, 2016;Harel & Bentin, 2009;Morrison & Schyns, 2001;Oliva & Schyns, 1997;Ozgen et al, 2006;Rotshtein et al, 2010;Schyns, 1998;Schyns & Oliva, 1994. For example, in Schyns and Oliva (1994), the perception of hybrids at short exposure duration of 30 ms was dominated by the HSF scene in 28% of the trials.…”
Section: Spatial Frequency Semantic Interferencesupporting
confidence: 70%
“…Although the prominent role of LSF information for rapid scene categorization has been extensively investigated and documented Schyns & Oliva, 1994; for a review see Hegdé, 2008;Kauffmann et al, 2014), there is also considerable experimental evidence of a predominant processing of HSF information even for very short stimuli exposure duration (Campagne et al, 2016;Harel & Bentin, 2009;Morrison & Schyns, 2001;Rotshtein, Schofield, Funes, & Humphreys, 2010;Schyns, 1998;Schyns & Oliva, 1999). Furthermore, many studies have shown that the use of spatial frequency information during the processing of complex stimuli such as scenes is highly flexible and depends on many factors such as stimulus exposure duration (Schyns & Oliva, 1994), category (e.g., Awasthi, Sowman, Friedman, & Williams, 2013;Collin & McMullen, 2005;Rotshtein et al, 2010;Vannucci, Viggiano, & Argenti, 2001), or task constraints (Abrams, Barbot, & Carrasco, 2010;Campagne et al, 2016;Caplette, West, Gomot, Gosselin, & Wicker, 2014;Fradcourt, Peyrin, Baciu, & Campagne, 2013;Morrison & Schyns, 2001;Ozgen, Payne, Sowden, & Schyns, 2006;Schyns & Oliva, 1999;Sowden, Özgen, Schyns, & Daoutis, 2003). For example, different spatial frequency bands would be used according to their diagnosticity to categorize a specific visual stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Both BAs 18 and 30 are located in the occipital lobe, whose primary structure is visual cortex center. Some researches indicated that visual cortex was associated with emotional activity and modulation [42, 43]. In view of the insufficient researches discussing the relationship between the occipital lobe and the improvement of clinical symptoms on patients with hypertension, we suppose that acupuncture at combined acupoints altered more brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Given these dynamic changes in subcortical and cortical circuits, as well as plasticity and the potential for change in the brain over the life course, there have been admirable attempts to develop a maturational index of the brain, similar to growth curves for height and weight (Brown et al 2012, Campagne et al 2016, Dosenbach et al 2010. For example, Brown and colleagues (2012) examined MRI-based structural changes in the brain to measure maturation in more than 800 three-to twenty-year-olds who were imaged at nine different sites (Figure 3a).…”
Section: When Does Psychological Ability Reach Adult Capacity?mentioning
confidence: 99%